PENGARUH ASUPAN PROTEIN HEWANI TERHADAP KELANCARAN ASI PADA IBU MENYUSUI DI PUSKESMAS KALIBAGOR - Wiji Oktanasari; Beby Yohana Okta Ayuningtyas (Ensiklopedia of Journal, 2026)
The achievement of good breast milk production is a key determinant of the success of exclusive breastfeeding. Nutritional status and adequate protein intake in postpartum mothers have a significant contribution to the process of breast milk formation and secretion. Breast milk nutrition can be influenced by maternal nutrient consumption, among other factors. Protein contributes to infant growth, body tissue formation, vital organ development, and immune defense. This cross-sectional quantitative study evaluated the association between maternal animal-protein intake and the adequacy of lactation. The target population comprised breastfeeding mothers registered at Kalibagor Community Health Center throughout the research period. Purposive sampling based on predefined eligibility criteria resulted in a final sample of 49 respondents. Animal protein intake was measured using the Food Frequency Questionnaire (FFQ) or the 24-hour Food Recall Method. This method records the types, portion sizes, and frequency of consumption of various animal protein sources (meat, eggs, fish, milk).  This study found that good animal protein intake was the most common category among respondents, with 21 respondents (42.9%), and good breast milk production smoothness was found in 26 breastfeeding mothers (53.1%). There was a significant relationship between animal protein intake and smooth breast milk production among breastfeeding mothers at the Kalibagor Community Health Center, indicated by a p-value of 0.008 and an odds ratio of 4.861. Relevant institutions should continue to intensify education on the role of animal protein intake in supporting smoother breast milk production among breastfeeding mothers.Keywords: Animal Protein, Breast Milk, Breastfeeding Mothers